Strategi Guru PAI dalam Memberikan Motivasi Belajar Siswa Kelas IV untuk Mewujudkan Tujuan Sekolah di SDIT Al Islam Kudus Tahun Ajaran 2022/2023 - Belia Citra Anjani; Julita Rika Amelia; Muhammad Nur Aminuddin Najib; M. Zaenal Abidin; Ummi Fadlilah; Heny Kusmawati (Journal on Education, 2023)
This research was conducted at SDIT Al Islam Kudus, with the title raised "Strategy of Islamic Religious Education Teachers in Providing Learning Motivation for Class IV Students to Realize School Goals at SDIT Al Islam Kudus Academic Year 2022/2023". Strategy is a plan that will be carried out to achieve a goal. As a teacher or educator, you must have a real plan and effort in carrying out each of your duties. Teachers are not only able to give or convey lessons (transfer of knowledge). But a teacher must also be able to provide enthusiasm or motivation, guidance, directions, solutions, and various other kinds of efforts that are expected to be able to provide understanding to students, so that they are not confused about what they have to prepare, do, and realize (realize) according to with what are the goals of themselves personally, teachers, parents, and the educational goals of their school. So that a goal can be realized, it is necessary to have a strategy that is able to provide an overview of the design (plan) which ultimately creates the best value and results for what you want to achieve. The teacher's strategy here, more specifically Islamic religious education teachers, is very important, it can even become a basis or benchmark to be able to see the extent to which each student they project is able to understand the goals expected by the school.